Predict A Person's Personality Based On The Shape of Handwriting of The Letters "i", "o", and "t" Using The Levenberg Marquardt Backpropagation Method - Heri Wijayanto; Annisa Mujahidah Robbani; I Gede Pasek Suta Wijaya; Fitri Bimantoro (Journal of Computer Science and Informatics Engineering (J-Cosine), 2021)
The literature shows that Graphology is common and relatively useful in our life. For example, as one of the job requirements. Professional organizations hire a professional handwriting analyst called Graphologist to analyze the characteristic traits of the candidates by identified their handwriting. However, the accuracy of handwriting analysis depends on how skilled the graphologist is, two graphologists which predict the same handwriting may give us a different result of the prediction. To improve the accuracy, we develop a system that can automatically predict a person’s personality based on the shape of the handwriting of the letters "i", "o", and "t" using the Levenberg Marquardt Backpropagation method. Based on this research we got the maximum accuracy by using 2 hidden layers. We got 71,42% of accuracy for the letter “i”, 76,92% of accuracy for the letter “o”, and 60% of accuracy for letter the “t”.